PENGARUH SELF CONCEPT TERHADAP RESILENSI PADA ORANGTUA ANAK BERKEBUTUHAN KHUSUS DI SLB NEGERI PEMBINA TINGKAT PROVINSI SUMATERA UTARA - Siska Dwi Ningsih; Sri Ramadhani (JURNAL PSYCHOMUTIARA, 2022)
Resilience is an individual's ability to respond in a healthy and productive way when dealing with adversity or trauma, which is very important for controlling the pressures of everyday life. In line with the resilience of parents who have children with special needs, most parents experience shock mixed with feelings of sadness, worry, anxiety, fear and anger when they first hear the diagnosis that their child has autism. One of the factors that influence resilience is self-concept. A positive self-concept will produce high resilience, and vice versa, a negative self-concept will produce low resilience. This research was conducted under the title The Influence of Self-concept on the Resilience of Parents of Children with Special Needs at the Elementary School Level in SLB Pembina North Sumatra Province. The purpose of this research is to find out whether there is an influence between self-concept on resilience. This research was conducted at SLB Pembina North Sumatra Province Elementary School Level with a total sample of 48 parents of children with special needs with a total population of 233 students. The data collection technique used a questionnaire with a Likert scale model and the sampling technique used Proportionate Stratified Random Sampling. The results of the study show that there is an influence of self-concept on the resilience of parents of children with special needs at the SD level at the State SLB Pembina North Sumatra Province. This is shown based on the results of a simple linear regression test with a value shown at a significance level of 0.000 <0.05. This means that the more positive a person's self-concept, the higher the resilience or conversely the more negative a person's self-concept, the lower the resilience.